O gesto corporal e a técnica pianística: um estudo aplicado à performance das obras The Tides Of Manaunaun e Aeolian Harp, de Cowell; Guero, de Lachenmann; Modelagem IX, de Zampronha - Juliana Gonçalves Marin (2020)
This research has as gerenal to show reflections of body gesture in the pianistic performance with a selection of 20th century works. From the theoretical reference of Gritten and King (2011), Leman and Godoy (2010), Windsor (2011), Jensenius (2010), Madeira and Scarduelli (2014), Chaib (2012), we seek to reflect about three gesture categories: sound-producing gestures, ancillary or facilitating gesture and cyclical gesture. Looking for a more gestural consciousness in regard to the sound and performative result, we applied the reflexions about this three categories in the study of the selected repertorie: The Tides of Manaunaun (1917) and Aeolian Harp (1923) from Henry Cowell (1897-1965), Guero (1969) from Helmut Lachenmann (1935-) and Modelagem IX (1996) from Edson Zampronha (1963-). The reflexions about body gestures generates a greater connection between piano technique and musical speech elements, that includes the gestural attitudes, poetic and figures of speech, making the performance more consistent. We did detailed descriptions about our decisions regarding piano technique, timbre explorations and body gestures, in addition to illustrating gestural trajectories through graphics and excerpts from the score. Through this research, we hope to help the piano community on the understanding and paths regarding the execution, interpretation and performance of this type of repertoire, in addition to stimulating the development of more works regarding this specific field.